Racism at school and beyond - Miti, Philip (The psychologist, 2021)
Boasting thorough original research, this book pioneers an interdisciplinary exploration of the legal structures and social policy under which young African Americans suffer frequent injustice. The legacy of racism for children: Psychology, law, and public policy I was the only black pupil in my year at junior school. This outstanding book carefully considers how such disparities have been exacerbated by US social and legal policy.
Gesehen am 15.09.2022
Keywords: Rezension